The concept of khiar rukyat according to Imam Abu Hanifah: An analysis of the concept, legal evidence, and implementation - Hidayat, Enang (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The validity of khiar rukyat (inspection option) according to Imam Abu Hanifah is considered absolute. However, the khiar rukyat he proposed is similar to bai al-gharar. The purpose of this research is to understand khiar rukyat according to Imam Abu Hanifah, the legal evidence, and its implementation in contemporary commercial contracts. This research falls under the category of normative Islamic legal research within the realm of doctrine (thought) using a conceptual approach. The data collection technique involves document analysis. The analysis utilizes prescriptive analysis of primary sources from the Hanafi school of thought, such as "Al-Mabsut" by al-Sarkhasi, "Tuhfat al-Fuqaha" by Alaudin al-Samarqandi, "Badai al-Sanai fi Tartib al-Sanai" by Alaudin al-Kasani, and others. This is supplemented by a review of previous research. The research findings indicate that the concept of khiar rukyat according to Imam Abu Hanifah is flexible because the connotation of rukyat is not only interpreted by observing the object of goods but also connotes that the object of goods can be touched and smelled. The evidence used by Imam Abu Hanifah regarding khiar rukyat includes hadith narrations from al-Baihaki from Makhul and from al-Daruqutni from Abu Hurairah. Additionally, there is a hadith narration from al-Baihaki from Abu Mulaikah concerning the right of khiar rukyat for the buyer only. Furthermore, the implementation of khiar rukyat in contemporary commercial contracts, such as online buying and selling, is difficult to execute due to customary practices (urf)Keywords: Khiar rukyat, Imam Abu Hanifah, Legal Evidence, Implementation.